1992
DOI: 10.1007/bf02285332
|View full text |Cite
|
Sign up to set email alerts
|

Covariance of adult size and development time in the parasitoid waspAphidius ervi in relation to the size of its host,Acyrthosiphon pisum

Abstract: SummaryAdult size (in terms of dry weight; DW) and development time (Tp) of thc solitary parasitoid Aphidius ervi Varied when reared in different nymphal instars of its host, apterous virginoparae of the pea aphid (Acyrthosiphon pisurn). Parasitoid DW increased with an increase in the DW of the host at parasitization, from the first to the third aphid instar. Female wasps gained 1.1 times more in DW than their male counterparts in all four host classes, but Tp did not significantly differ between the sexes. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 43 publications
6
72
0
1
Order By: Relevance
“…The body size of A. eadyi progeny increased with the host stage parasitised, generally supporting the studies by various authors (e.g., Liu 1985;Sequeira & Mackauer 1992). However, the quadratic relationship between host stages attacked and the size of the resulting progeny suggested that A. eadyi gain similar body size when attacking the fourth instar nymphs and adults.…”
Section: Discussionsupporting
confidence: 87%
“…The body size of A. eadyi progeny increased with the host stage parasitised, generally supporting the studies by various authors (e.g., Liu 1985;Sequeira & Mackauer 1992). However, the quadratic relationship between host stages attacked and the size of the resulting progeny suggested that A. eadyi gain similar body size when attacking the fourth instar nymphs and adults.…”
Section: Discussionsupporting
confidence: 87%
“…Natal host has been shown to influence odour preference, handling time and sex allocation behaviour, and to modify adult parasitoid morphology (Morris & Fellowes 2002;Fellowes et al 2005). Adult size is a highly flexible trait in many parasitoids that is determined by host size (Sequeira & Mackauer 1992b;Harvey et al 1994). This allows generalist parasitoids to use a broad range of host species.…”
Section: Discussionmentioning
confidence: 99%
“…The develop ment in pupa thus can be long, because the emerging adults on the mixed diet are large, and may require a longer time for metamorphosis (cf. Sequeira & Mackauer, 1992).…”
Section: Discussionmentioning
confidence: 99%